2022
DOI: 10.1093/humrep/deac194
|View full text |Cite
|
Sign up to set email alerts
|

Same-sex mothers’ experiences of equal treatment, parenting stress and disclosure to offspring: a population-based study of parenthood following identity-release sperm donation

Abstract: STUDY QUESTION What are the experiences of same-sex mothers following identity-release sperm donation regarding equal treatment in society, parenting stress and disclosure to child? SUMMARY ANSWER Mothers predominantly reported equal treatment in society, low levels of parenting stress and early disclosure of the donor conception to the child, and half of the couples had also informed the child of his/her right to obtain the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…The Well-being of Newborns: Studies have reported that babies born through gestational surrogacy do not show significant differences in physical, emotional, or cognitive development compared to babies born through other means [63,64].…”
mentioning
confidence: 99%
“…The Well-being of Newborns: Studies have reported that babies born through gestational surrogacy do not show significant differences in physical, emotional, or cognitive development compared to babies born through other means [63,64].…”
mentioning
confidence: 99%